2012
DOI: 10.1177/147470491201000311
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Premature Childbirth on Parental Bonding

Abstract: The development of an affectionate parent-infant bond is essential for a newborn infant's survival and development. However, from evolutionary theory it can be derived that parental bonding is not an automatic process, but dependent on infants' cues to reproductive potential and parents' access to resources. The purpose of the present study was to examine the process of bonding in a sample of Dutch mothers (n = 200) and fathers (n = 193) of full-term (n = 69), moderately premature (n = 68), and very premature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
2
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 48 publications
(72 reference statements)
2
46
2
12
Order By: Relevance
“…Because of a lack of norm-scores, we have to be careful with interpreting the PRAM-SBD. In a recent study with very preterm (born <31 weeks gestational age) and moderate preterm infants (born between 32–37 weeks gestational age) [55]), longitudinal analyses revealed that mothers’ PRAM-SBD scores decreased after moderately preterm delivery, whereas decreases in PRAM-SBD scores were observed in both parents after very preterm delivery. As lower PRAM-SBD scores represent stronger feelings of parent-infant connectedness, these findings suggest a higher degree of bonding after premature childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Because of a lack of norm-scores, we have to be careful with interpreting the PRAM-SBD. In a recent study with very preterm (born <31 weeks gestational age) and moderate preterm infants (born between 32–37 weeks gestational age) [55]), longitudinal analyses revealed that mothers’ PRAM-SBD scores decreased after moderately preterm delivery, whereas decreases in PRAM-SBD scores were observed in both parents after very preterm delivery. As lower PRAM-SBD scores represent stronger feelings of parent-infant connectedness, these findings suggest a higher degree of bonding after premature childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…These results hint at a need for a more differential view on bonding between parents and preterm babies in the NICU. Firstly, parents may not per se be at higher risk for bonding difficulties, although the infant's hospitalization could be a trigger or an additional risk factor for such difficulties (Hoffenkamp et al, 2012). And secondly, MT might be especially effective for parents who obstacle to forming healthy bonding with their babies.…”
Section: Mother-to-infant Bonding Scale (Mibs)mentioning
confidence: 99%
“…The appearance of preterm babies is perceived as less physically attractive than the features of full-terms: they are immature and show less infantile facial features (Goldberg & DiVitto, 2002; Hildebrandt & Fitzgerald, 1979; Hoffenkamp et al, 2012). …”
Section: Introductionmentioning
confidence: 99%